Теплопровідність Si нанониток з аморфною SiO2 обо-лонкою: молекулярно-динамічний розрахунок - Kuryliuk, V.V.; Semchuk, S.S.; Kuryliuk, A.M.; Kogutyuk, P.P. (Publishing house "Academperiodika", 2021)
The processes of thermal transport in Si nanowires covered with an amorphous SiO2 shell have been studied using the nonequilibrium molecular dynamics method. The influence of the amorphous layer thickness, radius of the crystalline silicon core, and temperature on the thermal conductivity of the nanowires is considered. It is found that the increase of the amorphous shell thickness diminishes the thermal conductivity in Si/SiO2 nanowires of the core-shell type. The results obtained also testify that the thermal conductivity of Si/SiO2 nanowires at 300 K increases with the cross-section area of the crystalline Si core. The temperature dependence of the thermal conductivity coefficient in Si/SiO2 nanowires of the core-shell type is found to be considerably weaker than that in crystalline silicon nanowires. This difference was shown to result from different dominant mechanisms of phonon scattering in those nanowires. The results obtained demonstrate that Si/SiO2 nanowires are a promising material for thermoelectric applications.